Electrochemical sensor for detecting Ganoderma boninense–infected oil palm leaves based on β-cyclodextrin functionalized with reduced graphene oxide–gold nanoparticles - Yusof, Nor Azah; Abdullah, Jaafar; Ithin, Nalisha; Abu Seman, Idris; Abd Rahman, Siti Fatimah (Institute of Electrical and Electronics Engineers, 2024)
Ganoderma boninense (G.boninense), a problematic fungus, causes major upper and basal stem rot (BSR) in palm trees. The interaction between G.boninense and oil palms generates several secondary metabolites as a defense mechanism, including sterol compounds such as stigmasterol. Herein, a sensitive electrochemical sensor based on beta-cyclodextrin, functionalized with reduced graphene oxide–gold nanoparticles (β-CD–rGO/AuNPs), was developed to detect stigmasterol, a biomarker for G.boninense-infected oil palm. The fabricated β-CD–rGO/AuNPs were characterized using Fourier transform infrared (FTIR) and Raman spectroscopy to provide detailed information on the chemical functional groups. The surface morphology of the modified electrode was examined using field emission scanning electron microscopy (FESEM) and high-resolution transmission electron microscopy, confirming the successful deposition of β-CD–rGO/AuNPs onto the screen-printed carbon electrode (SPCE) surface. Differential pulse voltammetry was used for the electrochemical detection of stigmasterol, revealing a decrease in peak current after stigmasterol displaced methylene blue (MB) from β-cyclodextrin cavities. Enhanced peak current of stigmasterol on β-CD–rGO/AuNPs-modified SPCE indicated the superior electrical conductivity and electrocatalytic activity of the integrated rGO and AuNPs, along with enhanced host–guest recognition and enrichment capacity of β-CD compared to bare SPCE and β-CD–rGO. Under optimal conditions, the developed electrochemical stigmasterol sensor demonstrated a response time of 30 s, excellent sensitivity, a linear range at concentration 2–30 µM, and a detection limit of 1.5 µM. Furthermore, the sensor demonstrated promising feasibility for real sample analysis, indicating its potential use in plant disease detection via electrochemical analysis of stigmasterol.